The Relationship Between Nursing Students' Solution-Oriented Levels and Their Attitudes to Dating Violence: Descriptive Research. - ÇOPUR, Ebru ÖZTÜRK; KARASU, Fatma; CAN, Zehra (Turkiye Klinikleri Journal of Nursing Sciences, 2022)
Objective: The aim of this study is to examine the relationship between nursing students' solution-oriented levels and their attitudes towards dating violence. Material and Methods: This descriptive study was conducted with 210 nursing students. "Personal Information Form, the Solution Focused Inventory (SFI), and the Dating Violence Scale (DVS)" were used to collect the data and ethics committee approval was obtained. The data were evaluated in SPSS 24.0 (Statistical Packet for Social Sciences for Windows) statistical program. Results: It was determined that 12.9% of the participants were exposed to violence in their dating relationship and 8.1% considered committing violence against their partner. The SFI mean score was 46.47±11.20 and the DVS mean score was 4.10±0.39 and the subscale mean scores was found 4.60±0.61 for physical violence, 4.56±0.56 for general violence, 3.61±0.60 for emotional violence, 3.64±0.40 for sexual violence, and 3.48±0.46 for economic violence. There was a positive weak correlation between the solution focality levels and dating violence. Conclusion: As a consequence, the present study found a positive weak correlation between the solution focality level and dating violence. It is believed that as the solution-focused thinking level increased, it will show a positive effect in decreasing dating violence attitude.